The importance of inflammatory biomarkers in detecting and managing latent tuberculosis infection - Harinisri Gunasekaran; Harinisri Gunasekaran; Uma Devi Ranganathan; Uma Devi Ranganathan; Uma Devi Ranganathan; Ramalingam Bethunaickan; Ramalingam Bethunaickan; Ramalingam Bethunaickan (Frontiers in Immunology)
Infection with Mycobacterium tuberculosis (Mtb) triggers an autoimmune-like response in the host leading to further complications. One of the major concerns in eliminating Tuberculosis (TB) is identifying individuals with Latent Tuberculosis Infection (LTBI) who serve as major reservoirs of Mtb making them the important target group for TB eradication. Since no gold standard tests are available for detecting LTBI, the global burden of LTBI cannot be precisely determined. Since LTBI poses several challenges to worldwide healthcare, managing LTBI must be the key priority to achieve a TB-free status. The inflammatory mediators play a major role in determining the outcome of the Mtb infection and also their levels seem to change according to the disease severity. Identification of inflammatory mediators and utilizing them as diagnostic biomarkers for detecting the various stages of TB disease might help identify the reservoirs of Mtb infection even before they become symptomatic so that preventative treatment can be started early. In summary, this review primarily focuses on exploring different inflammatory markers along the course of the Mtb infection. Identifying LTBI-specific biomarkers helps to identify individuals who are at higher risk of developing TB and preparing them to adhere to preventive therapy thus minimizing the global burden of TB.